Liver Stiffness Evaluation in Chronic Hepatitis C Patients with Cirrhosis before and after Direct-Acting Antivirals - Cristina Stasi; Stefano Brillanti (Microorganisms, 2024)
After the introduction of direct-acting antivirals, parallel significant clinical progress has been achieved in the assessment of liver fibrosis progression/regression before treatment and during the follow-up of the cirrhotic patients with chronic hepatitis C virus (HCV) infection. The evolution of chronic hepatitis C into liver cirrhosis is correlated with an extensive accumulation of the extracellular matrix, leading to the formation of large amounts of fibrotic tissues that, initially, are concentrated in periportal areas and, in the later stages, surround the nodules of regenerating hepatocytes. The progressive increase in the fibrotic matrix contributes to vascular disturbances (favoring the development of portal hypertension) and to microenvironmental changes. The four clinical stages of liver cirrhosis are predictors for different clinical scenarios. The wide-ranging functions of the liver require different methods for their assessment. The non-invasive evaluation using transient elastography is useful in determining the longitudinal modifications of fibrosis during and after treatment with direct-acting antivirals. The liver stiffness evaluation, known to have a wide range of values in cirrhotic patients, can offer different prognostic implications after sustained virological response. This review discusses the different time points of liver stiffness evaluation that appear to show a more well-defined propensity to identify adequate monitoring schedules for these patients.